Dataset of media practices for informational, educational, and entertainment purposes in Peru: Uses and gratifications approach - Mateus, Julio-César (2024)
This database consists of the Peruvian media diet in a post-pandemic context. Specifically, it examines how Peruvians define and utilise media to create environments for information, learning, and entertainment. Since the pandemic, the relationship that users have developed with the media has intensified and changed, fostering new uses and interactions. However, our data demonstrates that the Peruvian public maintains a critical role towards mass media (broadcasting model) [1], which motivates them to seek out media and platforms that cater to their interests and expectations. In this regard, we compare three axes of analysis (information, education, and entertainment), taking socio demographic variables, to produce a baseline that is useful for specific research projects. Through a quantitative approach we explored the expectations, decisions, forms of interaction, and satisfactions that users obtain in their relationship with the media, offering new theoretical insights based on emerging data, such as the level of planning in content consumption or the role that traditional media play in different age and socioeconomic groups.